2020
DOI: 10.1039/c9cc07029j
|View full text |Cite
|
Sign up to set email alerts
|

Polar nano-region structure in the oxynitride perovskite LaTiO2N

Abstract: Polar nano-region formation in the oxynitride perovskite LaTiO2N is demonstrated from PDF analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…This is similar to the findings by Fry and Woodward and provides a new avenue to explore in designing hybrid improper polar materials . The displacive disorder of the anion sites observed in bulk ceramic samples (here and Needs et al) is likely to disrupt tendencies for O 2– /F – ordering over the anion sites, but the possibility of local regions that are non-centrosymmetric (similar to recent reports in oxynitrides) has potential for the design of new materials with relaxor-like properties . Our use of the Rietveld method combined with bond valence penalties , can give additional chemical information for the structural analysis of systems with atoms of similar scattering lengths.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This is similar to the findings by Fry and Woodward and provides a new avenue to explore in designing hybrid improper polar materials . The displacive disorder of the anion sites observed in bulk ceramic samples (here and Needs et al) is likely to disrupt tendencies for O 2– /F – ordering over the anion sites, but the possibility of local regions that are non-centrosymmetric (similar to recent reports in oxynitrides) has potential for the design of new materials with relaxor-like properties . Our use of the Rietveld method combined with bond valence penalties , can give additional chemical information for the structural analysis of systems with atoms of similar scattering lengths.…”
Section: Discussionsupporting
confidence: 79%
“…However, this preference rarely gives long-range N 3– /O 2– order, and instead, a correlated order (comprising cis- anion chains) emerges . This lack of long-range site order is thought to disrupt long-range correlations between any polar displacement in the oxynitrides, , limiting the length scale of any polar region and can give polar nanoregions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pseudocubic perovskites all anion sites show similar coordination environments with cations, favouring total disorder of nitrogen and oxygen or partial order with local cis configuration of B −N bonds . The origin of ferroelectricity in tantalum and titanium perovskite oxynitrides is still under discussion, and large dielectric polarizability is ascribed to the presence of randomly oriented local dipoles induced by the cis order of nitrides in the B O 4 N 2 octahedra …”
Section: Figurementioning
confidence: 99%
“…The perovskite-type oxynitride, LaTiO 2 N, is an orthorhombic structure belonging to the Imma space group in which O and N atoms occupy random anion sites. Yamaura et al investigated the local structure of LaTiO 2 N using the extended X-ray absorption fine structure (EXAFS) and neutron pair distribution function (PDF) techniques . These analyses revealed that the local structure at short-range scales of r < 8 Å is polar, although the average structure is centrosymmetric.…”
Section: Introductionmentioning
confidence: 99%